Smart Wearable Devices for Healthcare - Kalpana K,; Geetha P,; Monalisa T,; Praveenya N,; Vaishnavi, (International Journal of Scientific Research in Science and Technology, 2025)
Wearable biosensors are gaining tremendous interest in the clinical and biological medical fields for their potential in providing patients with real-time diagnostic tools and time-sensitive information, non-invasive measurements of biochemical markers distributed in body fluids throughout the body. These sensors replace part of the equipment that can only be installed in hospitals and become a new choice for assessing human health. Herein, critical perspectives are put forward regarding wearable sensors in the future digital health monitoring industry. Moreover, the materials and processing technologies involved have also been discussed in recent years, along with their monitoring schemes and system-level integration technologies. Finally, the probability of wearable sensors being used in early disease detection is considerable. Thus, despite potential challenges, it is still quite promising for wearable sensors to come into production.
Keywords: Body sensors Smart sensor; Wearable electronics; Wearable sensor; Stretchable electronics Healthcare